Pengetahuan Remaja Putri Tentang Kanker Payudara Di SMA Negeri 1 Rambah Samo Kabupaten Rokan Hulu - Handayani, Eka Yuli (Jurnal Martenity and Neonatal, 2016)
According to the World health organization (WHO) breast cancer will be experienced by women as much as 8-9% in his life. Every year more than 580,000 new cases are found in many developing countries and approximately 372,000 patients die from the disease. Data obtained from the Ministry of Health stated number of breast cancer are detected in Indonesia reached 26 per 100,000 women. Data from Pekanbaru city health department, the incidence of breast cancer in the city of Pekanbaru in 2000 - 2004 amounted to 207 people. Breast cancer is a malignancy of cells - cells found in breast tissue. The aim of this study was to determine the knowledge of young women about breast cancer SMA Negeri 1 Rambah Samo Rokan Hulu. This type of research is descriptive. The population in this study were 208 people, 67 people sampled by simple random sampling. This type of data is primary data. Results of research knowledge young women about breast cancer majority knowledgeable enough categories numbered 28 persons (41.8%) and a good knowledge of minority numbering 19 people (28.3%). The conclusion of this study is that the overall level of knowledge of young women about breast cancer knowledgeable enough majority of 28 votes (41.8%). Saran, is expected to teenage girls to be more sensitive in knowing information about breast cancer, and for the institutions in order to further improve the quality of learning about breast cancer by adding books on breast cancer in the library and for researchers seklanjutnya hoped this research can be used as a comparison to other similar studies.